Influenza Classification Suite: An automated Galaxy workflow for rapid influenza sequence analysis. Issue 3 (16th February 2020) - Eisler, Diane; Fornika, Dan; Tindale, Lauren C.; Chan, Tracy; Sabaiduc, Suzana; Hickman, Rebecca; Chambers, Catharine; Krajden, Mel; Skowronski, Danuta M.; Jassem, Agatha; Hsiao, William
Abstract: Influenza viruses continually evolve to evade population immunity, and the different lineages are assigned into clades based on shared mutations. We have developed a publicly available computational workflow, the Influenza Classification Suite, for rapid clade mapping of sequenced influenza viruses. This suite provides a user‐friendly workflow implemented in Galaxy to automate clade calling and antigenic site extraction. Workflow input includes clade definition and amino acid index array files, which can be customized to identify any clades of interest. The Influenza Classification Suite provides rapid, high‐resolution understanding of circulating influenza strain evolution to inform influenza vaccine effectiveness and the need for potential vaccine reformulation.